2017
DOI: 10.1089/fpd.2016.2270
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Consumer Exposure toSalmonellaspp.,Campylobacterspp., and Shiga Toxin–ProducingEscherichia coliin Meat Products at Retail in the City of Sao Paulo, Brazil

Abstract: Meat products may be vehicles of bacterial pathogens to humans, and Salmonella spp., Campylobacter spp., and Shiga toxin-producing Escherichia coli (STEC) are the most relevant. The aim of this study was to generate data on prevalence of these three pathogens in 552 samples of meat products (hot dogs, pork sausages, raw ground beef, and raw chicken legs) sold at retail in the city of Sao Paulo, Brazil. Salmonella spp. was detected in 5.8% (32/552) of samples, comprising pork sausages 62.5% (20/32) and chicken … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 57 publications
3
11
1
Order By: Relevance
“…The most common serotype in retail raw meat products was S. Thompson. While this result was consistent to two previous studies conducted in Iran (Soltan-Dallal et al, 2010; Sodagari et al, 2015), it differed from other reports in which the dominant serotype was S. Hadar in Xinjiang, China (Yin et al, 2016), S. Enteritidis in Henan Province, China (Yang et al, 2013) and S. Typhimurium in Brazil (Ristori et al, 2017). Other serotypes recovered in this study included S. Agona, S. Typhimurium, S. Enteritidis, S. Kentucky, and S. Derby, which have all been previously found in food products (Ma̧ka et al, 2014; Shah et al, 2017; Wang et al, 2017).…”
Section: Resultssupporting
confidence: 83%
“…The most common serotype in retail raw meat products was S. Thompson. While this result was consistent to two previous studies conducted in Iran (Soltan-Dallal et al, 2010; Sodagari et al, 2015), it differed from other reports in which the dominant serotype was S. Hadar in Xinjiang, China (Yin et al, 2016), S. Enteritidis in Henan Province, China (Yang et al, 2013) and S. Typhimurium in Brazil (Ristori et al, 2017). Other serotypes recovered in this study included S. Agona, S. Typhimurium, S. Enteritidis, S. Kentucky, and S. Derby, which have all been previously found in food products (Ma̧ka et al, 2014; Shah et al, 2017; Wang et al, 2017).…”
Section: Resultssupporting
confidence: 83%
“…Of note, none of the 929 E. coli isolates harbored the aatA and/or aggR genes, thus indicating the absence of the EAEC pathotype among the meat samples analyzed (data not shown). The isolation of STEC and aEPEC from meat products observed in this study corroborates reports of previous studies performed in Brazilian cities, including São Paulo, Rio de Janeiro, Ribeirão Preto, Campinas, and São José do Rio Preto [17][18][19][20]. Regarding the classification of the E. coli isolates in the different phylo-groups, using a quadruplex PCR method [21], we found that five aEPEC isolates were assigned to phylo-group A, while the aEPEC serotype O105:H7 and STEC ONT:H46 were assigned to phylo-group B1 (Table 2).…”
supporting
confidence: 91%
“…Cold chain breakdown during transport in plant B resulted in 1.70 ± 0.57 and 1.50 ± 0.74 log MPN/g counts for shoulder and loin cuts, respectively. Data from microbiological mapping reports in Brazil describe higher counts in comparison with the present study in ground meat (2.38 log MPN/g) and meat products (1.96 log MPN/g) (Borowsky et al., 2007; Ristori et al., 2017). In contrast, reports by Prendergast et al.…”
Section: Resultscontrasting
confidence: 57%